1995
DOI: 10.1002/sim.4780140402
|View full text |Cite
|
Sign up to set email alerts
|

Methodological and statistical problems in the construction of composite measurement scales: A survey of six medical and epidemiological journals

Abstract: Composite measurement scales (CMS) are increasingly used in medicine to measure complex phenomena or concepts such as disease risk and severity, physical and psychological functioning and quality of life. To investigate the methodology currently used in the construction of CMS, we examined 46 studies recently published in six major medical and epidemiological journals. Important measurement properties such as measurement level, content and construct validity and reliability are often neglected. Statistical met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 39 publications
2
80
0
2
Order By: Relevance
“…Reliability is the property of a method of measurement that ensures that it is repeatable. 13 Reliability is at best difficult and perhaps impossible to determine for pain scales 1,19,20 because http://www.pediatrics.org/cgi/content/full/110/3/e33pain intensity does not remain constant long enough to allow inter-or intraobserver comparisons. Pain is a dynamic state and changes in intensity over brief periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability is the property of a method of measurement that ensures that it is repeatable. 13 Reliability is at best difficult and perhaps impossible to determine for pain scales 1,19,20 because http://www.pediatrics.org/cgi/content/full/110/3/e33pain intensity does not remain constant long enough to allow inter-or intraobserver comparisons. Pain is a dynamic state and changes in intensity over brief periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…13,33. 34 Logistic regression methods require a fixed follow-up period (e.g. 10 years) and the outcome is reduced to whether or not the subject developed CHD during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The number of factors retained was determined from eigenvalues greater than or equal to 1 [9]. Factor analysis with rotation enabled identification of the dimensions in the questionnaire, and showed that the items selected measured domains that were identical to those hypothesised at the outset.…”
Section: Test-retest Reliabilitymentioning
confidence: 99%
“…This concept, which cannot be measured by direct observation of the care provided, involves the identification of expectations, needs, perceptions, past experiences, opinions and attitudes of patients [4,7,8]. Several authors have thus considered that the assessment of satisfaction required an operational formalisation of the concept into dimensions with their constituent items making up questionnaires [7], and hence this rapidly entailed the need to assess the psychometric properties of such instruments [9].…”
Section: Introductionmentioning
confidence: 99%